Optimising dopant concentration of hole transport layer to achieve high efficiency and stability perovskite solar cells - Lim, Yi Jun (Nanyang Technological University, 2022)
Perovskite solar cells (PSCs) have gained much interest in the photovoltaic (PV) industry thanks to their high absorption efficiency, tuneable electronic properties, ease of fabrication, and high efficiency enable to reach up to 25.2% in 2020 which is close to mature Silicon Photovoltaic (PV) technologies. However, the instability of perovskite cells, especially the thermal stability, remains a challenge in the commercialization of perovskite solar cells. Investigations have shown that the possible root cause of instability might be due to the additives, such as Li-TFSI and t-BP, in the conventional Spiro-OMeTAD hole transport layer (HTL). The preliminary observations reveal that thermal instability is still observable regardless of different Li-TFSI and t-BP concentrations. Therefore, alternative doping using tris (pentafluoro phenyl) borane (TPFB) will be explored to achieve a balance between efficiency and long-term thermal stability in this current work. The results show that the optimized TPFB concentration was found at 0.02 mmole, as indicated by 77% retained PCE after being stored inside an oven (85 C, 10% RH) for 696 hours. In contrast, the conventional Spiro-OMeTAD doped with Li-TFSI and t-BP shows accelerate PCE drop. In-depth observations reveal that despite similar hole extraction capability of all Spiro-OMeTAD conditions (pristine, TPFB doped, Li-TFSI doped), an increase in hydrophobicity, higher conductivity, and retained amorphous phase of Spiro-doped TPFB HTL may contribute to the high efficiency and long-term thermal stability of the devices. The more robust properties of the TPFB doped HTL subsequently lead to retained underneath perovskite morphology and composition, in addition to their intact interface, ensuring efficient charge extraction in the device. These results show that the thermal stability of Spiro-OMeTAD based HTL can be tuned simply through dopant engineering to manipulate both the electrical and physical properties.